POLIO ERADICATION: THE BIGGEST PUBLIC HEALTH INTERVENTION - Fazal Ather (Khyber Medical University Journal, 2012)
Poliomyelitis is an infectious disease, epidemic and endemic throughout the world. It is caused by one of three types of an ultra-microscopic virus namely Wild Polio Virus type 1,2 and 3 (WPV1, WPV2 and WPV3).  World Health Assembly adopted a resolution to eradicate Polio in 1988.1-3 At the time there were more than 350,000 cases per year globally.